Postawy mieszkańców małych miejscowości wobec Unii Europejskiej na przykładzie Trzcianki - Pajak, Beata; Pawlukiewicz, Mariusz (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
Before the referendum on the Polish society accepting or opposing Poland’s accession to the EU, the diagnosis of social support for the process of European integration assumed particular significance. A mundane negotiation process and widespread information campaign resulted in the changes in the citizens’knowledge of the European structures, their emotions stirred by the accession process and their readiness to support Poland’s accession to the European Union. One of Polish towns served as an example to survey the attitudes of its inhabitants towards the European Union. The paper presents the methodology and results of this survey.